The Influence Of Customer Perceived Value And Attitude Toward Local Supermarket Choice - Kua, John Swee Beng (2014)
In the competitive environment of retailing, the income and popularity of grocery stores are much dependent on customer’s choice to their stores. Many studies have focused on shoppers on evaluating store attributes such as merchandise prices, store atmosphere, quality and store convenience that form their attitude toward store and in turn affect supermarket choice. Dalam persekitaran peruncitan yang kompetitif, pendapatan dan populariti stor runcit banyak bergantung kepada pilihan pengguna untuk memilih stor tersebut. Banyak kajian telah memberi tumpuan kepada pembeli yang menilai ciri-ciri stor seperti contoh harga barangan, persekitaran stor, kualiti and kemudahan stor yang akan membentuk sikap mereka terhadap stor yang kemudianya mempengaruhi pilihan stor pasaraya.